2007
DOI: 10.1093/jn/137.5.1244
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Dietary Flavonoid Intake and Major Food Sources of U.S. Adults ,2

Abstract: Estimating flavonoid intake is a first step toward documenting the protective effects of flavonoids against risk of chronic diseases. Although flavonoids are important dietary sources of antioxidants, insufficient data on the comprehensive food composition of flavonoids have delayed the assessment of dietary intake in a population. We aimed to estimate the dietary flavonoid intake in U.S. adults and its sociodemographic subgroups and to document major dietary sources of flavonoids. We expanded the recently rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
394
12
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(435 citation statements)
references
References 54 publications
(64 reference statements)
19
394
12
10
Order By: Relevance
“…This is not unexpected because the flavonoid density of the diet has been found to increase with age, income, female gender, and white race. (31) The correlations of intakes between FFQ and 4-day food diaries were good (r ¼ 0.76 for total flavonoids). Willett (32) suggests that when FFQs are compared with multiple records of diet, correlation coefficients may reach 0.6 to 0.7, but values of 0.8 to 0.9 are unlikely.…”
Section: Discussionmentioning
confidence: 90%
“…This is not unexpected because the flavonoid density of the diet has been found to increase with age, income, female gender, and white race. (31) The correlations of intakes between FFQ and 4-day food diaries were good (r ¼ 0.76 for total flavonoids). Willett (32) suggests that when FFQs are compared with multiple records of diet, correlation coefficients may reach 0.6 to 0.7, but values of 0.8 to 0.9 are unlikely.…”
Section: Discussionmentioning
confidence: 90%
“…CRP has been used as a sensitive predictor of acute cardiovascular events compared with other widely used biomarkers [27] . Several population based observational studies have reported that serum CRP concentrations are inversely associated with dietary intake of fruits, vegetables and tea, which are rich in polyphenolic antioxidants [28] . Increased MPO activity indicates an acute inflammation and leukocyte accumulation in heart tissues of the ISO-injected rats [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins intake in humans has been estimated to be between 3 and 215 mg/day (Chun et al 2007;Frankel et al 1995;Pérez-Jimenez et al 2011;Wu et al 2006). Most studies have shown very low bioavailability of anthocyanins based only on the measurement in plasma or urine of the original anthocyanins and their conjugated metabolites, glucuronidated, and sulfated anthocyanins (Manach et al 2005).…”
Section: Introductionmentioning
confidence: 99%